Immunoassays in agricultural biotechnology - Shan, Guomin (Hoboken, New Jersey : John Wiley & Sons, 2011)
"A very broad range of professionals are using immunoassay technology daily to analyze genetically engineered (GE) crops and related areas, and many of these professionals are completely new to this technology. There is a great need for users to have a book containing technical and practical guidance, and describing limitations and pitfalls of applying immunoassay in agricultural biotechnology. This book focuses on the application of immunoassays to GE plants and related areas. A group of international experts from government agencies, academics and industries, who have many years of related experience, contribute high quality chapters in their areas of expertise. This book covers topics including principles of immunoassay, antibody engineering in AgBiotech, current technologies (formats, kit development, manufacturing and quality control), method validation, applications in trait discovery and product development, applications in grain products and food processing, applications in environmental monitoring, automation and high throughput, reference materials, data interpretation and source of error, and future perspectives and challenges. In addition, to meet the practical needs for a variety of readers from different backgrounds, methods and protocols are included as well"-- Provided by publisher
1. Introduction -- 2. Principle of Immunoassays -- 3. Antibody Engineering in Agricultural Biotechnology -- 4. Microtiter Plate ELISA --5. Lateral Flow Devices -- 6. Immunoassay Method Validation -- 7. Reference Materials and Considerations -- 8. Automation of Immunoassays -- 9. Data Interpretation and Sources of Error -- 10. Immunoassay Applications in Trait Discovery, Product Development and Registration -- 11. Immunoassay Applications in Grain Products and Food Processing -- 12. Immunoassay Applications on Soil Monitoring -- 13. Immunoassay Applications in Plant-based Biopharma -- 14. Immunoassays in Veterinary Plant-made Vaccines -- 15. Immunoassay as a GE Detection Method In International Trade -- 16. Future Perspectives and Challenges
Includes bibliographical references and index
Keywords: Agricultural biotechnology; Immunoassay -- Methods